Periodization training focused on technical-tactical ability in young soccer players positively affects biochemical markers and game performance - Aquino, R. L. Q. T.; Cruz Gonçalves, L. G.; Palucci Vieira, L. H.; Oliveira, L. P.; Alves, G. F.; Pereira Santiago, P. R.; Puggina, E. F. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to investigate the effects of 22 weeks of periodized training, with an emphasis on technical-tactical ability, on indirect markers of muscle damage, and the on-field performance of young soccer players. Fifteen players (age 15.4 ± 0.2 years, height 172.8 ± 3.6 cm; body mass 61.9 ± 2.9 kg; % fat 11.7 ± 1.6; VO2max 48.67 ± 3.24 ml/kg/min) underwent 4 stages of evaluation: prepreparatory stage—T0; postpreparatory stage—T1; postcompetitive stage I—T2 and; postcompetitive stage II—T3. The plasmatic activity of creatine kinase (CK) and lactate dehydrogenase (LDH) were evaluated, as well as the on-field performance (movement patterns, tactical variables). Regarding the plasmatic activity of CK and LDH, there was a significant reduction (p = 0.05) throughout the periodization training (T0: 350 U·L-1; T3: 150 U·L-1). Significant increases were observed (p = 0.05) in the intensity of the game, high-intensity activities (HIA) (T0: 22%; T3: 27%), maximum speed (T0: 30 km/h; T3: 34 km/h) and tactical performance, team surface area (T0: 515 m2; T3: 683 m2), and spread (T0: 130 m; T3: 148 m). In addition, we found significant inverse correlations between the percentage variation of T0 to T3 in CK and LDH activities with percentage variation in high-intensity running (r = -0.85; p = 0.05 and r = -0.84; p < 0.01, respectively) and HIA (r = -0.71 and r = -0.70; p = 0.05, respectively) during the matches. We concluded that there was reduced activity in biochemical markers related to muscle damage, as well as increases in-game high-intensity performance and the tactical performance of the study participants. Furthermore, players who showed greater reduction in plasma activity of CK and LDH also obtained greater increases in-game high-intensity performance along the periodization. These results may contribute to the expansion and future consolidation of the knowledge of coaches and sport scientists to develop effective methodologies for training in soccer.